SNAKE BITE IN NON-DESCRIPT BULLOCK: A CASE REPORT - P.N. Bhagwat; P.R. Rathod; G.R. Gangane; N.D. Jadhav; G.M. Chigure; M.P. Sakhare (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A non-descript 5 years old male bullock was referred to Department of Veterinary Pathology, College of Veterinary and Animal Sciences, Parbhani, Maharashtra for conduct of post mortem examination. The gross pathological observations in the present case of snake bite were myonecrosis, subcutaneous lodgment of unclotted blood, ecchymotic hemorrhages at the site of bite. Histopathological examination of muscles revealed acute hemorrhages along with multifocal necrosis, spreading of RBCs with homogenization of skeletal muscles. Microscopically, Kidney showed vacuolar degeneration, multifocal necrotic changes, hemorrhagic cystic degenerative changes. Liver, spleen and lungs showed severe congestion. On the basis of history, clinical findings, gross and histopathological examination, the death of the animal was due to severe acute renal failure caused by viper snake bite.